Uso de um jogo didático como ferramenta avaliativa do ensino e aprendizagem de Química - CARVALHO, Elane de Jesus Guilherme de (2023)
The present work describes the application of a didactic game, based on the adaptation of the traditional board game, for reviewing and evaluating contents related to classification, balancing and calculation of chemical reactions. The activity was applied to 31 students of the 3rd year of high school, in a state public school Dr. Maroja Neto in the municipality of São Domingos do Capim-PA, providing an analysis of the development of learning in a different way from the traditional perspective. The research was developed during the supervised internship IV, with a qualitative and quantitative approach, comprising the stages of execution of the game in the classroom and consequently having as an evaluation analysis the questions of the game answered by students in teams. It was observed that the board game of chemical reactions was presented as a positive tool in order to motivate and challenge students to expose their learning in a playful and pleasant way.